Religião e histeria feminina : psiquiatria e religiosidade popular no Recife (1950-1959) - Mascena, Lúcia de Fátima Cordeiro Pires (2011)
This research aims al analyzing the peculiar aspects regarding to women‟s mental psychological and emotional disturbs diagnosed as hysterics in 1950 decade, in the Hospital de Alienados - Hospital for lunatics- in Recife city. Hence fonhards, one must understand the discourses made- produced by the social institutions intellectuals responsible for these women‟s fate- destination- withein society. This study- work-has considered has viewed as relevant for this analysis events concerning a certain Brazil- a Brasil‟s type. That was absorbing new ideas arisen from the American way of life and was living in full economical political and cultural effervescence: the so-called the golden years In that model. The concept concerning religiosity was used to adapt a new configuration. New religions proposils as well on spirit practices reproduced- multiplied themselves and adquired their affirmationaffirmed. Themselves specially in the great cities peripheries, in order to minimize the existential problems that affected society, mainly poor women. Based on in these aspects, this research points out the nervous women and the confirmed ones as a constant target for a discriminatory and repressing political-social system that actuated silently within society these affirmations statement are shown up through touching reports transcribed in their life stories. In these reports, their-women affective economical and social problems jut out and made them vulnerable, to hysterical outbreaks. One must emphasize, as well, also the friendships importance and meaning constructed, build up in these poor women‟s neighborhood who as they suffer a lot on account of their social exclusion and public policies abandonment, they identify them selves and give support each other in their difficulties arisen in their day by day lives, having in the majority of their cases misery as a background